The geographic distribution of unemployment-related benefits and CDEP scheme employment - Altman, Jon C., 1954-; Hunter, Boyd.; Australian National University. Centre for Aboriginal Economic Policy Research (Canberra : Australian National University, Centre for Aboriginal Economic Policy Research, 1996)
Analyses geography of unemployment-related benefits and Community Development Employment Projects (CEDP) scheme to provide insights into Indigenous labour market activity.
Bibliography: p. 23-24.
Keywords: Community Development Employment Projects (Australia); Aboriginal Australians -- Employment; Employment subsidies -- Australia; Torres Strait Islanders -- Employment; Unemployment -- Australia -- Regional disparities; Community development; Employment - Programs - Community Development Employment Projects (CDEP); Economics - Economic development; Australia